Assessment of amplifying effects of ridges spacing and height on nano-structured MSM photo-detectors - Masouleh, F.; Das, Narottam; Mashayekhi, H. (Springer New York LLC, 2014)
© 2014, Springer Science+Business Media New York. This paper presents the light transmission efficiency of metal–semiconductor–metal photo-detectors (MSM-PDs) using finite difference time-domain method. The absorption of MSM PDs can be enhanced with the aid of nano-grating coupled surface plasmon resonances at the design wavelength. The simulated results show that the light absorption enhancement of nano-grating assisted MSM-PD is ~9-times better than the conventional MSM-PD.